Sustainability of knowledge translation interventions in healthcare decision-making: a scoping review. (December 2015) - Tricco, Andrea; Ashoor, Huda; Cardoso, Roberta; MacDonald, Heather; Cogo, Elise; Kastner, Monika; Perrier, Laure; McKibbon, Ann; Grimshaw, Jeremy; Straus, Sharon
Abstract Background Knowledge translation (KT, also known as research utilization, and sometimes referring to implementation science) is a dynamic and iterative process that includes the synthesis, dissemination, exchange, and ethically sound application of knowledge to improve health. A KT intervention is one which facilitates the uptake of research. The long-term sustainability of KT interventions is unclear. We aimed to characterize KT interventions to manage chronic diseases that have been used for healthcare outcomes beyond 1 year or beyond the termination of initial grant funding. Methods We conducted a scoping review by searching MEDLINE, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Campbell from inception until February 2013. We included experimental, quasi-experimental, and observational studies providing information on the sustainability of KT interventions for managing chronic diseases in adults and focusing on end-users including patients, clinicians, public health officials, health service managers, and policy-makers. Articles were screened and abstracted by two reviewers, independently. The data were charted and results described narratively. Results We included 62 studies reported in 103 publications (total 260, 688 patients) plus 41 companion reports after screening 12, 328 titles and abstracts and 464 full-text articles. More than half of the studies were randomized controlled trials (RCTs). The duration of the KT intervention ranged from 61 to 522 weeks. Nine chronic conditions were examined across the studies, such as diabetes (34 %), cardiovascular disease (28 %), and hypertension (16 %). Thirteen KT interventions were reported across the studies. Patient education was the most commonly examined (20 %), followed by self-management (17 %). Most studies (61 %) focused on patient-level outcomes (e.g. disease severity), while 31 % included system-level outcomes (e.g. number of eye examinations), and 8 % used both. The interventions were aimed at the patient (58 %), health system (28 %), and healthcare personnel (14 %) levels. Conclusions We found few studies focusing on the sustainability of KT interventions. Most of the included studies focused on patient-level outcomes and patient-level KT interventions. A future systematic review can be conducted of the RCTs to examine the impact of sustainable KT interventions on health outcomes.